Easy Coding in Biology: Pilot Workshop Design and Experiences from Block-Based Programming with in Secondary Education - Schmidthaler, Eva; Stäter, Rebecca; Cápay, Martin; Ludwig, Matthias; Lavicza, Zsolt (Journal of research in science, mathematics and technology education, 2023)
Block-based coding is a way to teach Computer Science (CS) concepts and Computational Thinking (CT) skills to K-12 students. Nowadays, there are more and more educational applications (learning apps) to teach programming in STEM subjects, but detailed studies on which and how these can be used successfully in Biology classes are still lacking, because apps and tasks promoting CS and CT concepts in combination with biological teaching content are missing. This mixed-method study aims to close this gap and presents six elaborated exercises of the workshop “Easy Coding in Biology”, employing two task formats (TF), Building Cubes and Drone AR, of the new learning app . The app utilizes block-based coding and an additional augmented reality (AR) function to describe several topics in secondary education, for example in the subject Biology. After presenting the workshop and task design, preliminary results of the successful use of the app and the tasks are presented. The pilot workshop was carried out with 51 participants at a Slovakian grammar school. After the implementation in class, 34 students filled in a questionnaire, consisting of open-ended and closed-ended questions. Qualitative data shows on the one hand AR malfunctions and on the other that participants liked the workshop concept. Quantitative findings indicate that the introduced TF Building Cubes and Drone AR of have the potential to successfully convey CS and CT concepts in Biology. In addition, the tasks encouraged the female participants in particular to work together because they found the tasks/app interesting, motivating, and fun.